Pengaruh Strategi Pembelajaran Peta Pikiran terhadap Motivasi Belajar dan Hasil Belajar Pendidikan Agama Hindu dan Budi Pekerti Siswa Kelas V di Sekolah Dasar Nomor 6 Benoa - I Kadek Bharata Dwyq Saputra; I Ketut Sudarsana; I Made Wiguna Yasa (Kamaya: Jurnal Ilmu Agama, 2023)
Motivation and student learning outcomes are still problems in Sekolah Dasar Nomor 6 Benoa, especially in the subjects of Hinduism and Moral Education. Improvements are still being carried out, which is by implementing a mind map learning strategy. The mind map learning strategy provides an opportunity for students to record the information they find during the learning process in a fun way. The purpose of this study was to analyze and explain (1) the effect of mind map learning strategies on the learning motivation of Hindu Religious Education and Characteristics of fifth-grade students at Sekolah Dasar Nomor 6 Benoa, (2) the effect of mind map learning strategies on learning outcomes of Hindu Religious Education and Characteristics of fifth-grade students at Sekolah Dasar Nomor 6 Benoa. This research was quasi-experimental with a non-equivalent control group pretest-posttest design. The instruments used in this study were questionnaires and tests. Mancova was used to test hypotheses I and II. Based on the results of the analysis, the average score of students' learning motivation in the experimental class was greater than that of the control class (78.63 > 69.33). In addition, the average score of student learning outcomes also shows that the average score in the experimental class is greater than the control class (78.90 > 64.77). The results of the hypothesis testing show that: (1) there is a significant influence between mind map learning strategies on the learning motivation of Hindu Religious Education and Characteristics of fifth-grade students at Sekolah Dasar Nomor 6 Benoa, (2) there is a significant influence between mind map learning strategies on learning outcomes of Hindu Religious Education and Characteristics of fifth-grade students at Sekolah Dasar Nomor 6 Benoa.